Pemasyarakatan Teknologi Polikultur Udang Windu Penaeaus monodon Fabr., Ikan Bandeng Chanos chanos Forskal dan Rumput Laut Gracillaria verrucosa di Tambak - Early Septiningsih; Suwardi Tahe (Universitas Hasanuddin, 2020)
The research was aimed to community pond in Borimasunggu, Maros, South Sulawesi. Aiming to socialize the polyculture technology of tiger shrimp, milk fish and seaweed. Using 3 ponds each measuring 1 ha. used post larva and milkfish seeds with an average weight of 0.056 ± 0.006 g and 75 ± 2.1 g respectively. While the seaweed seeds used are gracillaria verrucosa. Seaweed spreading is done 30 days earlier then spreading tiger shrimp and milk fish. Each ponds is scattered: A = 1,500 kg of seaweed + 30,000 tiger shrimp + 1,500 milkfish; B = 1,500 kg of seaweed + 30,000 tiger prawns; C = 1,500 kg of seaweed + 1,500 milkfish with 120 days maintenance time. Daily growth rate in plot A = (tiger shrimp = 5.66%, milkfish = 1.84% and seaweed = 2.3%) and production of 165 kg of tiger shrimp, 417 kg of milkfish and 4,285.7 kg of seaweed. Daily growth rate in plot B = (tiger shrimp = 5.21%; seaweed = 2.2%) and production of 127 kg of tiger shrimp, 3,985.7 kg of seaweed. While the growth rate in ponds C = milkfish = 1.91% and seaweed = 1.08% with a production of 450 kg of milkfish and 3,085 kg of seaweed. From the results of the economic analysis of the three ponds it turns out that in ponds A provides higher production and income followed by ponds B and ponds C.